A fluorometric assay to determine labile copper(II) ions in serum - Maares, Maria; Haupt, Alessia; Schüßler, Christoph; Kulike-Koczula, Marcel; Hackler, Julian; Keil, Claudia; Mohr, Isabelle; Schomburg, Lutz; Süssmuth, Roderich D.; Zischka, Hans; Merle, Uta; Haase, Hajo (Scientific reports, 2023)
Labile copper(II) ions (Cu2+) in serum are considered to be readily available for cellular uptake and to constitute the biologically active Cu2+ species in the blood. It might also be suitable to reflect copper dyshomeostasis during diseases such as Wilson’s disease (WD) or neurological disorders. So far, no direct quantification method has been described to determine this small Cu2+ subset. This study introduces a fluorometric high throughput assay using the novel Cu2+ binding fluoresceine-peptide sensor FP4 (Kd of the Cu2+-FP4-complex 0.38 pM) to determine labile Cu2+ in human and rat serum. ...